Effect of Transplanting Dates and Training Systems on Fruit, Seed Yield and Quality Attributes in Tomato (Solanum Lycopersicum) Under Protected Conditions - MANISH KUMAR; SANTOSH GUPTA; PALAK SHARMA; SAILJA THAKUR (Seed Research, 2026)
The experiment was undertaken during kharif season of 2019-20, inside a plastic greenhouse at experimental farm and laboratory conditions of department of Seed Science and Technology, Dr. Y S P University of Horticulture and Forestry, Nauni, Solan, H.P. in order to determine the effect of planting dates and training systems on fruit, seed yield and quality in tomato cv. Solan Lalima. The treatments comprised of four planting dates (transplanting on 1st April, 15th April, 1st May and 15th May) and four training systems (single stem, two stem, four stem, no training). The different treatments showed differential response but overall transplanting on 1st April with two stem training system was significantly superior or at par with best results for various yield and quality traits in tomato like number of flowers per cluster, number of fruits per cluster, fruit set percent, total number of fruits per plant, average fruit weight, fruit yield, 1000 seed weight, number of seeds per fruit, seed yield, percent seed germination, seedling length, seedling dry weight, SVI-I & II, cold test and accelerated aging test. Hence, for higher quality fresh fruit and quality seed produce, treatment combination comprising of transplanting on 1st April with two stem training system can be recommended for growing tomato under protected conditions on commercial scale in mid hills of Himachal Pradesh.